Uncertainty and Irreproducibility of Triboelectricity Based on Interface Mechanochemistry - Fatti, Giulio; Kim, Hyunseung; Sohn, Changwan; Park, Minah; Lim, Yeong Won; Li, Zhuohan; Park, Kwi Il; Szlufarska, Izabela; Ko, Hyunseok; Jeong, Chang Kyu; Cho, Sung Beom (Physical Review Letters, 2023)
Triboelectrification mechanism is still not understood, despite centuries of investigations. Here, we propose a model showing that mechanochemistry is key to elucidate triboelectrification fundamental properties. Studying contact between gold and silicate glasses, we observe that the experimental triboelectric output is subject to large variations and polarity inversions. First principles analysis shows that electronic transfer is activated by mechanochemistry and the tribopolarity is determined by the termination exposed to contact, depending on the material composition, which can result in different charging at the macroscale. The electron transfer mechanism is driven by the interface barrier dynamics, regulated by mechanical forces. The model provides a unified framework to explain several experimental observations, including the systematic variations in the triboelectric output and the mixed positive-negative "mosaic"charging patterns, and paves the way to the theoretical prediction of the triboelectric properties.
Keywords: Electronic transfers; Exposed to; First principles; Fundamental properties; Mechano-chemistry; Polarity inversion; Principle analysis; Silicate glass; Triboelectrification; Uncertainty